Out of the box : strategies for achieving profits today and growth tomorrow through web services - Hagel, John. (Boston, Massachusetts : Harvard Business School Press, 2002)
This authoritative text examines how a company's information technology can help or hinder its ability to manage short-term costs and achieve long-term growth. Provides a clear view of the business implications of Web services: its distinct capabilities, its power to deliver near-term profits, and its potential to drive long-term growth.
Includes bibliographical references and index.
oif 17/02/15
Loan
Keywords: Electronic commerce; World Wide Web; Internet; Strategic planning